DAYA TARIK OBJEK WISATA MASJID RAYA RENGAT KABUPATEN INDRAGIRI HULU - Faradhiba Ulfa Hasanah; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Rengat Grand Mosque is the first historical mosque which was built in Rengat, this mosque was established in the 21st century of the sultanate, namely Sultan Isa Mudoyatsyah. Rengat Grand Mosque is a religious tourist attraction. Visitors can enjoy the history and experience of religious tours at the Rengat Grand Mosque. Rengat Grand Mosque has fulfilled the standard of attraction in a tourist destination that can be measured with 3 components, namely Something To See, Something To Do, and Something To Buy. This study uses a qualitative descriptive method to analyze problems based on interview, observation and documentation data collection techniques which are then drawn conclusions. The subjects of this study were obtained from the results of interviews with key informants namely, the Heirs of the Royal Family and the Manager of the Rengat Grand Mosque. From the results of research that has been done, shows that the Rengat Grand Mosque has several attractions, namely the unique architecture of the roof building in the form of Limasan, Mihrab bearing seroja flowers, Nadzor Shower, Pilgrimage, Islamic Da'wah, and Dodol Kedondong as typical souvenirs of Rengat. The obstacles in increasing the attractiveness of the Rengat Grand Mosque are less publicized through various media so that it is only known by word of mouth. Keywords: Attractiveness, Tourist Attraction